LEVELS OF LEARNER AUTONOMY IN ONLINE LEARNING AMONG INDONESIAN EFL TERTIARY STUDENTS - Daflizar Daflizar; Okti Wilymafidini (University of Kuningan, 2026)
In the 21st century, promoting learner autonomy has become a central objective in education, especially in the context of language learning. Encouraging students to take responsibility for their learning is believed to enhance their motivation and engagement in learning English. One increasingly popular tool that supports this goal is the English Online Platform, which facilitates autonomous learning by offering easily accessible resources and opportunities to improve English proficiency. Although many studies on learner autonomy have been conducted in Indonesia, most have focused on conventional classroom settings, with relatively few addressing autonomy in online learning contexts. This study investigated the readiness of Indonesian EFL undergraduate students for autonomous learning in online English courses and examined whether their perceptions of autonomy differed by gender or year of study. Data were obtained from 164 English education students across seven higher education institutions in three provinces in Indonesia through an online questionnaire. Both descriptive and inferential statistics were used to analyze the data. The findings revealed that students demonstrated moderate to high levels of autonomy across the four dimensions: self-control, self-reflection, self-interaction, and self-motivation. Among the dimensions, self-reflection was rated the highest, which indicates that students strongly perceived themselves as reflective learners who could assess their performance and articulate reasons behind their successes and failures, while self-interaction was the lowest, suggesting their limited confidence in online communication and collaboration. While gender did not significantly affect students’ perceptions, differences were noted based on years of study. The study offers implications for EFL teachers and higher education institutions in the Indonesian context.